Epitaxial Growth of Bi2Se3 Infrared Transparent Conductive Film and Heterojunction Diode by Molecular Beam Epitaxy - Chuai, Ya-Hui; Zhu, Chao; Yue, Dan; Bai, Yu (Frontiers in Chemistry, 2022)
Epitaxial n-type infrared transparent conductive Bi2Se3 thin film was cultivated by molecular beam epitaxy (MBE) method on Al2O3 (001) substrate. The orientation between Bi2Se3 and the substrate is Bi2Se3(001)//Al2O3(1 2¯ 10). Conducting mechanism ensued the small-polaron hopping mechanism, with an activation energy of 34 meV. The film demonstrates conductivity of n-type, and the resistivity is 7 × 10−4 Ωcm at room temperature. The Film exhibits an excellent carrier mobility of 1,015 cm2/Vs at room temperature and retains optical transparency in the near-infrared (>70%) and far-infrared (>85%) ranges. To the best of our knowledge, the Bi2Se3 film yields the best result in the realm of n-type Infrared transparent conductive thin films generated through either physical or chemical methods. To demonstrate the application of such films, we produced N-Bi2Se3/P-CuScO2 heterojunction diode device, the ∼3.3 V threshold voltage of which conformed fairly well with the CuScO2 bandgap value. The high optical transparency and conductivity of Bi2Se3 film make it very promising for optoelectronic applications, where a wide wavelength range from near-infrared to far-infrared is required.